Influence of Successive Subcultures and Hormone Concentrations on Somaclonal Variation in Tissue-Culture-Derived Pineapple (Ananas comosus var. MD2) - Rahman, Zuraida Ab; Abbas, Hartinee; Othman, Ayu Nazreena (European Journal of Applied Sciences, 2025)
Somaclonal variation is a major limitation in the micropropagation of pineapple (Ananas comosus var. MD2), as it reduces clonal fidelity and impacts commercial planting material. This study investigated the influence of successive subcultures and plant growth regulator (PGR) concentrations on morphological variation. Successive subcultures showed no abnormalities up to the 8th passage, but abnormal plantlets began to emerge at the 10th subculture (0.30%) and progressively increased to 0.90% at the 14th subculture. At the 7th subculture, increasing benzylaminopurine (BAP) concentrations caused a dose-dependent rise in abnormalities: 0% at 1 mg L⁻¹, 0.20% at 5 mg L⁻¹, 1% at 7.5 mg L⁻¹, and 3% at 10 mg L⁻¹. Higher BAP levels also shifted plant morphology from predominantly spineless to spiny forms, with full-margin spines reaching 12% at 10 mg L⁻¹. Abnormalities included stunted shoots, distorted leaves, and spiny margins. These findings indicate that extended subculturing and supra-optimal hormone levels induce somaclonal variation, compromising true-to-type regeneration. Limiting subculture cycles (≤8 passages) and maintaining lower PGR concentrations (around 1 mg L⁻¹) are recommended to preserve clonal fidelity in MD2 pineapple micropropagation.